Are they the same? Disentangling the concepts of implementation science research and population scale-up - Karen Lee; Heather McKay; Melanie Crane; Andrew Milat; Luke Wolfenden; Nicole M Rankin; Rachel Sutherland; Adrian Bauman (Sax Institute, 2024)
A new discipline, implementation science, has emerged in recent years. This has resulted in confusion between what 'implementation science' is and how it differs from real-world scale-up of health interventions. While there is considerable overlap, in this perspective, we seek to highlight some of the differences between these two concepts in relation to their origin, drivers, research methods and implications for population impact and practice. We recognise that implementation science generates new information on optimal methods and strategies to facilitate the uptake of evidence-based practices. This new knowledge can be used as part of any scaling-up endeavour. However, real-world scale-up is influenced to a much greater extent by political and strategic needs and key actors and generally requires the support of governments or large agencies that can fund population-level scale-up. Furthermore, scale-up often occurs in the absence of any evidence of effectiveness. Therefore, while implementation science and scale-up both ultimately aim to facilitate the uptake of interventions to improve population health, their immediate intentions differ, and these distinctions are worth highlighting for policymakers and researchers.